Bridging the Gap: Micro-credentials for Development: UNESCO Chairs Policy Brief Form - Under the III World Higher Education Conference (WHEC 2021) Type: Collective X - McGreal, Rory; Mackintosh, Wayne; Cox, Glenda; Olcott, Don (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2022)
This paper describes current trends and issues in implementing micro-credentials. The Covid19 epidemic, combined with the increasing cost of higher education; employer concerns about graduate skills and competencies; increasing inequities in access; and student frustrations about lack of job opportunities have all been a catalyst for universities, colleges, independent credentialing agencies, and leaders of national qualification frameworks to rethink the broader credentials continuum in terms of open education and micro-credentials. Students desire more options at lower costs to combine their education and training for jobs.  Employers want entry-level employees with better skills and capacity to learn. As a result, major colleges and universities are now actively engaged in granting and/or recognising micro-credentials. Standardising qualifications based on time competencies is an essential requirement for credit transfer among institutions. Micro-credentials are important in ensuring the acceptance and stackability of credentials from different institutions, while providing employers with a secure and unalterable permanent digital record of applicants' abilities to perform skills of high value in the workplace. The OERu (Open Educational Resources universitas) provides an example of how one international consortium is supporting SDG4: Education for All by implementing micro-credentials allowing for maximum transferability among institutions in different countries. The lesson for strategic leaders is simplicity. Micro-credentials should be well Integrated into current institutional programs, rendered easy-to-use with clear validation metrics, providing a value-added benefit for all stakeholders.  A list of recommendations to institutions, governments, UNESCO and Non-Governmental Organizations (NGOs) is provided.